2018
DOI: 10.6060/mhc180382z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anion on the C-Cl Bond Cleavage of Toxic Organochlorides Electrocatalyzed by Co(II) Porphyrin

Abstract: An electrochemically reduced Co(I) meso-tetraphenylporphyrin anion was examined in electron reductive dechlorination of environmental harmful organochlorides by using various supporting electrolytes. The tunable reactivities were formed when different supporting electrolytes were tested. For the first time the experimental and mechanistic investigations were combined, what provided useful information for future rational molecular design towards highly efficient removal of environmental harmful organochloride c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Several recent scientific reports have indicated that most of the health problems caused by chronic consumption of cigarette smoke can be attributed to dysfunction of the immune system. Many medical reports dating back to the 1960s suggest that an increase in smoking-related diseases can be caused by tobacco, which changes the response of the immune system and inflammatory reaction [9]. Cigarette smoking changes many immune system functions in both human and laboratory animals, and these changes can be observed in both cellular and humoral immune responses, numerous medical reports have suggested that impair the immune system may be attributed to increased exposure to cigarette smoke [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent scientific reports have indicated that most of the health problems caused by chronic consumption of cigarette smoke can be attributed to dysfunction of the immune system. Many medical reports dating back to the 1960s suggest that an increase in smoking-related diseases can be caused by tobacco, which changes the response of the immune system and inflammatory reaction [9]. Cigarette smoking changes many immune system functions in both human and laboratory animals, and these changes can be observed in both cellular and humoral immune responses, numerous medical reports have suggested that impair the immune system may be attributed to increased exposure to cigarette smoke [10].…”
Section: Introductionmentioning
confidence: 99%